Investigation of deep sea shelf sandbank dynamics driven by highly energetic tidal flows - Harshinie Karunarathna (Marine Geology, 2016)
In this paper we describe a numerical modelling study carried out to investigate the prevailing sediment dynamics of two large sandbanks located at a site designated for future development of tidal stream energy extraction, in the Inner Sound Channel of Pentland Firth, Scotland, UK. A calibrated and validated 3D Delft3D hydrodynamic model covering Pentland Firth channel was combined with a morphodynamic model. The sea bed changes occurring around the sandbanks during a period of two spring-neap tidal cycles are described and discussed in detail. It was found that both sandbanks, which are located in a deep shelf region (depths > 18 m), are morphodynamically active and their existence and integrity are strongly linked with the existing hydrodynamic regime.